A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans. (30th May 2016) - Yang, Xiaoxiang; Cui, Hui; Cheng, Jiasen; Xie, Jiatao; Jiang, Daohong; Hsiang, Tom; Fu, Yanping
Summary: Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum . Previously, a conidiation‐deficient mutant, ZS‐1N22225, was screened from a T‐DNA insertional library of C. minitans . CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T‐DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino‐terminal citron homology domain and a central clathrin homology domain, as observed for other Vam6p/Vps39p family proteins. Abnormal fragmented vacuoles were observed in ΔCmVps39 under light microscopy and transmission electron microscopy, and ΔCmVps39 showed impairment in autophagy. ΔCmVps39 also exhibited significantly reduced hyphal development, poor conidiation and decreased sclerotial mycoparasitism. In addition, deletion of CmVps39 affected osmotic adaptation, pH homeostasis and cell wall integrity. Taken together, our results suggest that CmVps39 has an essential function in vacuolar morphology, autophagy, fungal development and mycoparasitism in C. minitans .